Вплив тиристорного перетворювача на пульсації електромагнітного моменту асинхронного двигуна при параметричному управлінні - Лобов, В'ячеслав Йосипович; Лобова, Карина Віталіївна (НТУ "ХПІ", 2017)
Представлені розрахунки та фізичне моделювання коливальних складових електромагнітного моменту при зміні параметрів асинхронного електродвигуна, елементів силових схем перетворювачів, побудованих на резисторно-тиристорних модулях. Установлено, що величина пульсацій електромагнітного моменту у квазісталих режимах залежить від вибраної силової схеми статорного і роторного комутаторів перетворювача, складу елементів, що входять до них, і схеми їх з’єднання, зміни величини кутів відкриття вентилями, способи їх управління, частота обертання ротора, параметри механізму – моменти статичний та інерції. Запропоновано використовувати для дослідження узагальнену схему параметричного управління асинхронного електродвигуна.

The conducted researches allowed to reveal the peculiarities of the effect of the parameters of the elements of various types of power circuits of the parametric control converters on the vibrational components of the electromagnetic torque of an induction electric motor. Calculations and physical modeling have been performed, it has been possible to establish the conditions for the occurrence of electromagnetic pulsations and to determine the ways of their elimination. It was found that the magnitude of pulsations of the electromagnetic moment of an induction electric motor in quasi-permanent modes depends on the selected power circuit of the converter's stator and rotor commutators, the composition of the elements included in them, and the connection circuits. Comparison of calculated and experimental waveform when starting induction electric motors indicates that the pulsation of the electromagnetic torque is affected by: the size of the opening angle of the valves, their control methods, the rotor speed, the parameters of the electric motor and the mechanism are static and inertial moments. At the same time, it was revealed that the use of resistor-thyristor modules in the power circuits of the stator and rotary commutators reduces the magnitude of the pulsation of the electromagnetic torque of the induction electric motor. Increase the value of its maximum and average torques. Limit the magnitude of the shock and alternating torques when it starts and the transition from one speed to another.
The thyristor converter influence on the pulsations of the electromagnetic torque of the induction motor at parametrical control
Keywords: асинхронний електродвигун; узагальнена схема; тиристорний перетворювач; АД; ЕМ; резисторно-тиристорний модуль; статорний комутатор; роторний комутатор; induction electric motor; generalized circuit; thyristor converter